Deposition features of heterovalent iron (Fe2 + and Fe3 +) in the liver in alcoholic and nonalcoholic steatohepatitis - V. A. Tumanskiy; S. V. Fen' (Zaporozhye State Medical University, 2015)
Aim. The article describes morphological characteristics of the heterovalent iron compounds (ferric (Fe3 +) iron, ferrous (Fe2 +) iron) deposition in the acini of the liver. Methods and results. Using histochemical methods, features of accumulation of ferrous (Fe2 +) and ferric (Fe3 +) iron in hepatic acinar zone were studied in the trephine biopsy and autopsy liver material of 35 patients suffering from alcoholic steatohepatitis (ASH) of different (S1, S2, S3) degree, and trephine liver biopsy of 15 patients suffering from moderate S2 non-alcoholic steatohepatitis (NASH). It was found that in the ASH Fe3 + deposition in liver macrophages and hepatocytes predominates over Fe2 +accumulation, and Fe3 + extracellular localization is defined primarily in the areas of liver steatonecrosis. The intensity of Fe3 + and Fe2 + deposition in the liver increases from G2 to G4 degree with increasing of severity of ASH from S1 to S3. In patients with NASH of moderate degree, accumulation of Fe3 + and Fe2 + is determined in liver macrophages and hepatocytes in mild G2 degree. Conclusions. It is assumed that the deposition of Fe3 + and Fe2 + in liver cells and extracellular matrix most likely contributes to the ASH development.